Physicochemical and organoleptic properties of cookies incorporated with legume flours - Sushma Thongram (Cogent Food & Agriculture, 2016)
In developing countries like India, with increasing urbanization, the demand for processed food and bakery products particularly cookies command wide popularity in both urban and rural mass. Hence, an attempt was made to develop functionally and nutritionally improved cookies and the influence of the partial replacement of the wheat flour by legume on the quality characteristic of cookies was analyzed. Six blends were prepared by homogenously mixing chickpea flour, pigeon pea, moong bean flour, and cowpea flour with wheat flour in the percentage proportions: 100, 25:75, 25:75, 25:75, 25:75, and 10:10:10:10:60 (CPF:WWF, PF:WWF, MF:WWF, CF:WWF, and CPF:PF:MF:CF:WWF) and later used to make cookies. Chemical and functional properties of the composite flours and chemical as well as sensory characteristics of cookies made from the above combinations were determined. The incorporation of legume flour significantly affected the physical, chemical, and phytonutrient parameters of the cookies. The results revealed that functional properties, viz. water absorption capacity, oil absorption capacity, and swelling property, increased with addition of legume flours. The physical analysis revealed that the diameter and height increased with the incorporation of legume flour. The results of the proximate composition showed that the A6 possesses highest percentage of proteins (13.42%) and crude fat (22.90%), A5 contains maximum value of crude fiber (2.10%) and DPPH radical scavenging activity (55.47%), A1 showed maximum moisture (10.60%), A2 total phenolic content (6.14 TAE mg/100 g), and A3 showed maximum ash (3.66%). Statistical results revealed that the addition of selected pulse flours and a combination of these whole flours do not have a significant effect (p > 0.05) on the sensory characteristics of cookies.